Implementasi Cobit 4.1 Untuk Mengukur Tingkat Kematangan Penyampaian Layanan Teknologi Informasi Di Sistem Informasi Akademik (Studi Kasus: Universitas Sriwijaya) - Nabila Rizky Oktadini; Putri Eka Sevtiyuni; Muhammad Ali Buchari (Jurnal Sistem Informasi, 2020)
Measuring the maturity of Technology and Information Systems in Higher Education is motivated by an awareness of the strategic value and importance of technology and information systems in supporting academic activities programs. In general, the measurement of the maturity of the process of delivering IT services in an information system must provide complete information or information systems and information systems related to academic requirements. Academic of Sriwijaya University, and provide suggestions for Sriwijaya University, and provide advice for Sriwijaya University, as well as provide suggestions for improvements in the use of IT in the future based on the COBIT 4.1 framework.